The Implementation of Pancasila Ideological Values through the Citizent Projet Model to Prevent Radicalism - Maksum, Hafidh; Anwar , Faisal; Arasyid, Harunnun; Abubakar; Saleh, Muhamad; Anwar; Usman, Muhammad (Yayasan Ilomata, 2025)
Radicalism can emerge in parts of society due to various factors, such as religious, political, economic, and other forms of radical actions. This study discusses the implementation of Pancasila ideology with project citizen model values as a means to prevent the spread of radicalism in Indonesia. The aim of the study is to explore how all elements of the nation can apply Pancasila ideology values with model project citizen in daily life, as citizens and members of the state, to prevent the growth of radicalism. The research used a literature review method. The findings show that an increased understanding of Pancasila ideology values with model project citizen can help counter radical actions that threaten national unity and the integrity of the Republic of Indonesia. The study concludes that as radical ideology continues to grow, the best solution for the nation is to apply the values of Pancasila ideology, which has been agreed upon as the national consensus. It is recommended that the implementation of Pancasila ideology values be used model project citizen as a preventive measure against radicalism in Indonesia. The ideology of Pancasila especially in the practice of Pancasila itself in daily life.